AI chatbots in sport psychology: a paradigm shift or a complementary tool? - Saraç, H.; Polat, I. G. (Baltic Journal of Sport and Health Sciences, 2025)
The integration of AI chatbots represents a potential paradigm shift in the field of sport and exercise psychology. This perspective article addressed the potential roles, benefits, challenges, and limitations of AI chatbots in applied sport psychology. To illustrate potential integration, a hypothetical case representing chatbot-assisted pre-competition anxiety management was presented. The study highlights AI chatbots` potential to enhance accessibility, cost-effectiveness, personalized support, and long-term monitoring. However, their implementation requires a critical examination of ethical, professional, technical, and user-related factors. Based on the current knowledge, they should be regarded as complementary rather than a replacement for human experts. In conclusion, AI chatbots show potential as supportive tools in applied sport psychology. Further research is necessary to assess their short- and long-term impacts and to establish evidence-based guidelines for their integration.